Efficiency improvement water bottling plant using SOP, 5S and SLP - Reyes-Saldaña, Pablo; Alvarado-Portugal, Sebastián; León Chávarri, Claudia Carolina; Chavez-Ugaz, Rafael (LACCEI, 2025)
The bottled water industry performs a crucial role in preventing waterborne diseases and ensuring the overall well-being of people worldwide. Unfortunately, low efficiency remains a significant challenge within the industry, which could jeopardize the ability to meet current demand. Therefore, this study is important as it proposes an improvement in operational efficiency through a conceptual model. This model begins by preventing defective materials from entering the process, then increases the capacity of the bottleneck, and finally reduces defective in-process products during transport. This model includes standard operating procedures, 5S and SLP tools and achieved a significant reduction of 82.14% in unproductive time and a 46.61% reduction in the number of defective bottles. These changes primarily improved efficiency by 8,8%. Initial results were obtained through pilot tests, which were projected to provide a comprehensive solution for the system in Arena simulator. Finally, the economic impact was evaluated using RISK simulator, which confirmed the profitability of the improvements, with a positive Net Present Value ranging from 1.13 US to 1.94 US.